If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x = 9(2x) + -3(4x) + -1 Remove parenthesis around (2x) 5x = 9 * 2x + -3(4x) + -1 Multiply 9 * 2 5x = 18x + -3(4x) + -1 Remove parenthesis around (4x) 5x = 18x + -3 * 4x + -1 Multiply -3 * 4 5x = 18x + -12x + -1 Reorder the terms: 5x = -1 + 18x + -12x Combine like terms: 18x + -12x = 6x 5x = -1 + 6x Solving 5x = -1 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 5x + -6x = -1 + 6x + -6x Combine like terms: 5x + -6x = -1x -1x = -1 + 6x + -6x Combine like terms: 6x + -6x = 0 -1x = -1 + 0 -1x = -1 Divide each side by '-1'. x = 1 Simplifying x = 1
| -78+66x-21x+20-47+88x=10x-36x+18 | | -3m=8n-1 | | -5r+8=43 | | 9k-7=21-3k | | 1.7t+8-1.62=0.4t-0.32+8 | | 7h+3=0 | | 37=x+3+2x+2+5x | | m=2-1.25(-1) | | 5y-3+y=90 | | 80-3k=5k+8 | | -22+14x-33+10x-77+25x=88-14x+65-5+35 | | 2(2d-7)=(2+4d)2 | | 2x+32=6x+8 | | w^2+2w-310=0 | | 2w-9=-17 | | 5w^2+30w+6=0 | | 16x(7-x)=160 | | 8x-2=28x+13 | | 9*(3x)+4*(3x)=30x+5 | | (4x+34)=(7x+10) | | 9y+5y+20=62 | | 3x-10x+16=9-12x-28 | | 6(x-1)=3(x+1) | | 5xy(x+y)= | | (y-2)(y+4)=0 | | 6=2(7-c) | | y=16-6 | | 8-23x-14=9x-30x-6 | | 25-1.25x=16-.5x | | 15x-20=14x-21 | | 7+x(4)=16 | | -5n-8=16m |